The Effect Of Transactional Leadership, Incentives, Instrinctive Motivation And Hofstede Culture On Working Practice (Study Of DLH Empat Lawang Case) - Husin, Anwar; Syah, Lin Yan Syah; Samsuddin, Harun (Multidisciplinary Journals, 2024)
This research aims to determine and analyze the influence of Transactional Leadership, Incentives,Intrinsic Motivation, and Hofstede Culture on Work Performance at the Empat Lawang RegencyEnvironmental Service Office, both partially and simultaneously. The research method used in thisresearch is a quantitative method using questionnaires distributed to respondents. Test data qualityusing validity tests, reliability tests, normality tests. The analysis used is multiple linear regression analysis, partial test, simultaneous test, and coefficient of determination. The results of thediscussion and analysis show that Transactional Leadership, Incentives and Intrinsic Motivation are proven to have a significant effect on work performance. Meanwhile, Hofstede Culture does not have a significant effect on Job Performance at the Empat Lawang Regency Environmental Service Office.